Program Kemitraan Pengembangan Desa Wisata Di Desa Noepesu Kecamatan Miomaffo Barat Kabupaten Timor Tengah Utara - Fritantus, Yohanes; Minggu, Pionisius; Rembu, Yoakim (Empowerment, 2022)
Noepesu Village is one of the villages located in the West Miomaffo District, North Central Timor Regency, and is one of the border villages bordering the South Central Timor district. Geographically, Noepesu Village still has a beautiful environment that makes this village very beautiful. The objectives of implementing community service activities include a). provide an understanding related to “tourism awareness” for village officials and administrators of BUMDES Noepesu, b). provide understanding and assistance to Village Apparatus and BUMDES Management regarding archive administration management, as well as social media as village promotion media based on customer satisfaction. In order to achieve the objectives listed above, the method of activity used is conducting field observations, carrying out counseling and mentoring with lecture and question and answer methods. The results of service activities are first, contacting partners and field observations, second, preparing tools and materials to carry out activities, and third, carrying out counseling and assistance to partner target groups.